The roles of FGF21 and GDF15 in mediating the mitochondrial integrated stress response - Jena, Jayashree; García-Peña, Luis Miguel; Pereira, Renata O. (Frontiers in Endocrinology, 2023)
Various models of mitochondrial stress result in induction of the stress-responsive cytokines fibroblast growth factor 21 (FGF21) and growth differentiation factor 15 (GDF15). This is an adaptive mechanism downstream the mitochondrial integrated stress response frequently associated with improvements in systemic metabolic health. Both FGF21 and GDF15 have been shown to modulate energy balance and glucose homeostasis, and their pharmacological administration leads to promising beneficial effects against obesity and associated metabolic diseases in pre-clinical models. Furthermore, endogenous upregulation of FGF21 and GDF15 is associated with resistance to diet-induced obesity (DIO), improved glucose homeostasis and increased insulin sensitivity. In this review, we highlight several studies on transgenic mouse models of mitochondrial stress and will compare the specific roles played by FGF21 and GDF15 on the systemic metabolic adaptations reported in these models.